2019
DOI: 10.1186/s12891-019-2851-2
|View full text |Cite
|
Sign up to set email alerts
|

Bone mesenchymal stem cell therapy for ovariectomized osteoporotic rats: a systematic review and meta-analysis

Abstract: BackgroundPrevious studies have found that bone mesenchymal stem cells (BMSCs) were capable of self-replication, multi-differentiation, and regeneration. The aim of this study was to carry out a systematic review and meta-analysis of the efficacy of BMSC therapy for ovariectomized rats.MethodsThe PubMed, Embase, Web of Science, China National Knowledge Infrastructure, VIP, and Chinese Sinomed databases were searched systematically from their initiation date to October 5, 2018. Two researchers independently scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Our previous study demonstrated that osthole significantly stimulated osteoblast differentiation and bone formation by the activation of Wnt/β-catenin-Bmp2 signaling [ 24 ]. The previous meta-analysis showed that BMSCs promote bone cell maturation, ossification, and restore bone mechanical properties in osteoporotic fractures [ 25 ]. Although osthole can promote bone formation, its effect on bone resorption and the underlying mechanism is yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated that osthole significantly stimulated osteoblast differentiation and bone formation by the activation of Wnt/β-catenin-Bmp2 signaling [ 24 ]. The previous meta-analysis showed that BMSCs promote bone cell maturation, ossification, and restore bone mechanical properties in osteoporotic fractures [ 25 ]. Although osthole can promote bone formation, its effect on bone resorption and the underlying mechanism is yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis can result in fractures and may increase economic cost and societal burden [3]. Previously, bone marrow mesenchymal stem cells (BMSCs) were administered as seed cells to improve BMD and used for tissue engineering [4]. However, the proliferation ability of BMSCs was limited, especially in older patients.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study found that Osthole signi cantly stimulated osteoblast differentiation and bone formation by inducing the activation of Wnt/β-catenin-Bmp2 signaling [24] . And our previous metaanalysis of basic reports shows that BMSCs can promote bone call maturation, ossi cation and restore bone mechanical properties in osteoporotic fractures [25] . Although Osthole can promote bone formation, its effect on bone resorption and underlying mechanism remain unknown.…”
Section: Introductionmentioning
confidence: 96%